0935 The Role of PTSD and Major Depressive Symptoms in Nightmare Frequency and Distress. (27th April 2018) - Wakschal, E; Boland, E; Gehrman, P; Haynes, P
Abstract: Introduction: PTSD and major depressive disorder (MDD) are highly comorbid. It is well established that nightmares are a key feature of PTSD, though the role that depression plays in the expression of this symptom is less clear. The present study attempted to elucidate the relationship between depression, PTSD, nightmare frequency, and nightmare distress. Methods: Data were obtained from 63 male veterans who met criteria for PTSD and MDD. Nightmare distress and frequency were measured through daily sleep diaries, and psychiatric symptoms were assessed using the Hamilton Rating Scale for Depression (HRSD) and Clinician Administered PTSD Scale (CAPS). Results: When sleep items on the HRSD and CAPS were omitted, nightmare frequency was significantly associated with CAPS scores ( p =.02) but not HRSD scores ( p =.28), and nightmare distress was associated with HRSD scores at trend level ( p =.07) but not significantly related to CAPS scores ( p =.61). When sleep items were included in the HRSD and CAPS, the only change was that nightmare distress was significantly associated with HRSD scores ( p= . 03). Conclusion: These findings suggest that increased PTSD severity contributes to greater number of nightmares, but not the level of distress associated with them. The fact that nightmare distress was associated with depression suggests that depression and insomnia (as assessed via the HRDS sleep items) may be implicated in the more debilitating aspects of nightmares in PTSD patients. Further research is necessary to determine the precise nature of this relationship. Support (If Any): Funding for this research was supported by Department of Defense #W81XWH-08-2-0121 (PI: Haynes) and American Sleep Medicine Foundation #37-CA-06 (PI: Haynes). Analysis and presentation of this research supported by: Department of Veterans Affairs IK2-CX001501 (PI: Boland).